Control Strategy for A Smart Grid-Hybrid Controller for Renewable Energy using Artificial Neuro and Fuzzy Intelligent System - Muhammad usman Haider Khan; Muhammad Siddique; M. Kamran Liaquat Bhatti; Waqar Tahir; Muhammad Kashif (Pakistan Journal of Engineering & Technology, 2020)
Energy generation using renewable energy resources is increasing with the passage of the time due to the fear of depleting energy resources and global warming. In Pakistan, the whole consumption of electricity in residential and business areas is nearly equal to 40%. More than 5% of energy needs are fulfilled by liquid natural fuel and town gasoline consumption within the residential and industrial sectors. Integration of the renewable resources may cause tripping issues and control of this tripping with the help of conventional controlling methods is time-consuming and wastage of energy. In this research paper, SEC based ANFIS controller for control strategy has been implemented. For this purpose, we used DVR for finding the fault and compensate the voltage drop to the maximum value to avoid tripping. Dynamic programming is used to design a controller which compares the voltage of both renewable resources with the nominal voltage and the triggers the control switches of Bridge through PWM according to the nominal voltage. The model shows that the accuracy and efficiency of the proposed solution are much better than the conventional controller.